2002
DOI: 10.1080/09622935020138208
|View full text |Cite
|
Sign up to set email alerts
|

Implication of extracellular zinc exclusion by recombinant human calprotectin (MRP8 and MRP14) from target cells in its apoptosis‐inducing activity

Abstract: BACKGROUND: Calprotectin is a calcium-binding and zinc-binding protein complex that is abundant in the cytosol of neutrophils. This factor is composed of 8 and 14 kDa subunits, which have also been termed migration inhibitory factor-related proteins MRP8 and MRP14. We previously reported that rat calprotectin purified from inflammatory neutrophils induces apoptosis of various tumor cells or normal fibroblasts in a zinc-reversible manner. AIM: The present study was undertaken to elucidate which subunit is respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 37 publications
6
43
2
Order By: Relevance
“…60) As a result, the cytotoxicity of the 14 kD subunit was detected from 10 mM, whereas that of the 8 kD subunit was marginal at the same concentration. On the other hand, the mixture of both induced almost complete cell death at 5 mM: calprotectin has higher specific activity than either subunit individually.…”
Section: )mentioning
confidence: 89%
See 1 more Smart Citation
“…60) As a result, the cytotoxicity of the 14 kD subunit was detected from 10 mM, whereas that of the 8 kD subunit was marginal at the same concentration. On the other hand, the mixture of both induced almost complete cell death at 5 mM: calprotectin has higher specific activity than either subunit individually.…”
Section: )mentioning
confidence: 89%
“…[66][67][68] To examine this possibility, the cytotoxic activity of calprotectin against EL-4 cells was tested under conditions where physical contact between the factor and the cells was precluded by a dialysis membrane. 60) As the result, the factor induced cell death even when contact was hindered. The membrane-impermeable zinc cheletor, Diethylenetriaminepentaacetic acid (DTPA), also induced cell death in a similar way to calprotectin.…”
Section: Fig 2 Effect Of Calprotectin On the Growth Of Various Tumomentioning
confidence: 99%
“…DTPA, the membrane-impermeable metal ion chelator, induces apoptosis through the depletion of extracellular zinc ion [24]. S100A8/A9 also binds zinc with high affinity, and it has been reported that the antimicrobial activity and the cell death (apoptosis)-inducing activity of S100A8/A9 are inhibited by the presence of zinc [10,24,38].…”
Section: Discussionmentioning
confidence: 99%
“…DTPA, the membrane-impermeable metal ion chelator, induces apoptosis through the depletion of extracellular zinc ion [24]. S100A8/A9 also binds zinc with high affinity, and it has been reported that the antimicrobial activity and the cell death (apoptosis)-inducing activity of S100A8/A9 are inhibited by the presence of zinc [10,24,38]. However, based on the observations that Zn 2ϩ and Cu 2ϩ did not completely reverse the apoptotic effect of S100A8/A9; the changes in the morphology of both cell lines treated by S100A8/A9 were different from those observed with DTPA; and the time-course of S100A8/A9-induced apoptosis differed from that induced by DTPA, we conclude that S100A8/A9 induces apoptosis by a mechanism that is not simple as a result of zinc sequestration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation